Systematic Literature Review: Peran Pendidikan Matematika Realistik dalam Meningkatkan Kemampuan Pemahaman Konsep - Faiza Izzati Mufti (International Forum of Researchers and Lecturers, 2024)
The low understanding of mathematical concepts experienced by students also has an impact on students' ability to solve problems related to mathematics because the concepts taught by teachers are never found in everyday life. Therefore, a learning approach is needed that encourages students to construct their own mathematical concepts based on experiences that occur in everyday life. The research method used in this research is Systematic Literature Review (SLR). The data collection process includes collecting and analyzing every published article and book that discusses mathematical concepts and the application of Realistic Mathematics Education (RME). The journals used in this research are national and international journals indexed by SINTA and SCOPUS. Research findings show that the RME approach has an important role in improving students' ability to understand mathematical concepts in several materials at every level of education.